MANAJEMEN PERPUSTAKAAN (Studi di Yayasan Perguruan Madinatussalam Kec. Percut Sei Tuan) - meriani meriani (Universitas Islam Negeri Sumatera Utara Medan, 2018)
This research aims at: 1) find out how planning, 2) organizing, 3) Implementation, 4) 5) supervision and Constraints in the process management of library in College Foundation Madinatussalam Sei Tuan subdistrict of his whip. This research was conducted at the Foundation College Madinatusssalam Percut Sei Tuan Subdistrict. The approach in this study using qualitative descriptive approach. As Informants in this study is the head of the madrasa, the head of the library and the Deputy Head of the madrasa Curriculum Section. Data collection techniques using several methods, methods of observation, Interview and documentation. Data analysis was done by reduction of data, Data and Cereal Drawdown conclusion. Whereas the examination of the validity of the Data is carried out by means of credibility, dependence and Assertiveness. The results showed that: planning the management of the library in the conventional starting in 2006. These include planning, non Human Resources include: service, collections and infrastructure. This includes organizing forms of organizational structure, personnel qualification standard library as well as unity of command and coordination led by the head of the madrasa is assisted by the Deputy Head of the madrasa. Penggerakan related job description is done by the head of the library and only one officer. Supervision in the management of the library is carried out on the human resources (HR) and facilities and infrastructure related to the supervision exercised by the head of the madrasa and head of the library. Some of the obstacles that impede the management process includes the limitations of knowledge, insights into library, lack of encouragement of the head of the madrasa in the management process and infrastructure are inadequate.Keywords: Library Management, library, Foundation.